PENGAWASAN DINAS PENDIDIKAN TERHADAP KINERJA PENILIK PAUD DI ROKAN HULU TAHUN 2017 - Santi Anggraini; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research entitled "Supervision of the Education Office on Performance of Early Childhood Education Observers in Rokan Hulu in 2017" This research was motivated by the existence of Ministerial Regulation Number 20 of 2003 concerning the supervisory functional position system which explained that the supervisor is an education staff whose main task is to carry out quality control and evaluation activities the impact of the PAUD program. The formulation of the problem in this study is "How is the supervision of the education office on the performance of PAUD inspectors in the rokan hulu in 2017". The method used in this study is a qualitative method that describes data descriptively. Data collection techniques used were interviews, observation and documentation. While the data sources used are primary data obtained from the location of the study in the form of research informants and subsequently supported by secondary data in the form of data documents. The results of this study indicate that the results of the inspector's performance at the Rokan Hulu district education office must be increased again because there are still many things that make it difficult for PAUD institutions to develop their institutions and the constraints posed by the Rokan Hulu education department are that there are still many PAUDs that are not optimally developed. In carrying out their duties and evaluating the performance of inspectors from upstream education services, training is carried out to develop performance. Inspectors provide incentives for inspectors whose performance is good Keywords: Supervision, Service, Oversight Performance